2021
DOI: 10.1097/ncq.0000000000000574
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Burnout Syndrome and Work Environment Impact Patient Safety Grade

Abstract: Background: Burnout impacts nurses' health as well as brain structures and functions including cognitive function, which could lead to work performance and patient safety issues. Yet, few organization-level factors related to patient safety have been identified. Purpose: This study examined nurse-reported patient safety grade and its relationship to both burnout and the nursing work environment. Methods: A cross-sectional electronic survey was conducted among nurses (N = 928) in acute care Alabama hospitals. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…A favorable nurse work environment is an important organizational characteristic associated with positive nurse and patient outcomes. Favorable professional nurse work environments have been associated with lower nurse burnout 1,2 and lower occupational injuries, 3,4 in addition to higher job satisfaction 5,6 and lower intent to leave the job 5,6 . Exceptional nurse work environments are associated with higher nurse-rated quality of care 2 and lower rates of adverse events 1,5 and patient mortality 5-7 .…”
Section: Introductionmentioning
confidence: 99%
“…A favorable nurse work environment is an important organizational characteristic associated with positive nurse and patient outcomes. Favorable professional nurse work environments have been associated with lower nurse burnout 1,2 and lower occupational injuries, 3,4 in addition to higher job satisfaction 5,6 and lower intent to leave the job 5,6 . Exceptional nurse work environments are associated with higher nurse-rated quality of care 2 and lower rates of adverse events 1,5 and patient mortality 5-7 .…”
Section: Introductionmentioning
confidence: 99%
“…As nurses are found to be more engaged in work through new challenges and interests, the workplace environment must possess supportive characteristics that are dynamic and responsive to the needs of the nurses. Healthcare organizations can significantly reduce burnout when the work environment has been improved at the organizational level, thereby reducing negative patient safety performance (Montgomery et al, 2022). The service-oriented feature of the profession, while it already creates enormous demand among nurses to provide only quality and safe care, should investigate policies and guidelines that protect them from exhaustion and disengagement at work (Caramanzana, 2020;Feliciano et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…([ICN], 2022). Additional studies have shown that nurses report higher levels of personal burnout and work-related burnout vs client-related burnout (Montgomery et al, 2022;Creedy et al, 2017). This is promising since front-line nurse have direct patient interactions on a regular basis.…”
Section: Variablesmentioning
confidence: 99%